2014
DOI: 10.1515/cclm-2012-0792
|View full text |Cite
|
Sign up to set email alerts
|

Formation of nitri- and nitrosylhemoglobin in systems modeling the Maillard reaction

Abstract: The assumption was made that intermediates of the Hb glycation reaction play an important role both in vinyl group nitration and in heme iron nitrosylation. Oxygen content in reaction medium is an important factor influencing these processes. These effects can play an important role in pathogenesis of the diseases connected with carbonyl, oxidative and nitrosative stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…•− ) released during Hb auto-oxidation [34]. These reactive compounds can interact with each other, and with SH groups, heme, and non-heme iron, which leads to shifts in the thioldisulfide equilibrium and in Hb state [41,161]. Free iron ions and the ones included in heme and non-heme complexes play an important role in the coupling of glycation and ROS formation processes [162].…”
Section: Relationship Of Carbonyl Stress With Oxidative and Nitrosatimentioning
confidence: 99%
See 1 more Smart Citation
“…•− ) released during Hb auto-oxidation [34]. These reactive compounds can interact with each other, and with SH groups, heme, and non-heme iron, which leads to shifts in the thioldisulfide equilibrium and in Hb state [41,161]. Free iron ions and the ones included in heme and non-heme complexes play an important role in the coupling of glycation and ROS formation processes [162].…”
Section: Relationship Of Carbonyl Stress With Oxidative and Nitrosatimentioning
confidence: 99%
“…•− and NO. We have previously investigated the effect of the NO donors on the non-enzymatic Hb modification with MG [41,161]. It was found that S-nitrosoglutathione (GSNO) increased the formation of radical intermediates of the lysine reaction with MG, which lead to Hb reduction and nitrosylation.…”
Section: Relationship Of Carbonyl Stress With Oxidative and Nitrosatimentioning
confidence: 99%
“…According to the pertinent literature on the subject, α-oxoaldehyde such as methylglyoxal plays an important role in the non-enzymatic and enzymatic production of free radicals in biological systems [5,17,20,[30][31][32]. For example, the free radical derivatives can be formed in the reaction of methylglyoxal -induced protein glycation [18].…”
Section: Formation Of Superoxide and Organic Free Radicals In The Reamentioning
confidence: 99%
“…Leghemoglobin is glycosylating as other hemoglobins [54]. Thus, another way for nitrosyl Lb to be formed in nodules could be the joint action of reactive nitrogen species and reactive carbonyl compounds (simultaneous display of nitrosative and carbonyl stress) similar to the case of mammalian Hb [55,56]. ROS and RNS could be formed in legume nodules under various negative factors, whereas different kinds of stress have similar affect [57,58].…”
Section: Dinitrosyl Iron Complexes and Plant Hemoglobinsmentioning
confidence: 99%